Smooth muscle dysfunction in the pre-inflammation site in stenotic Crohn’s-like colitis: implication of mechanical stress in bowel dysfunction in gut inflammation - Johnson, John C.; Geesala, Ramasatyaveni; Zhang, Ke; Lin, You-Min; M’Koma, Amosy E.; Shi, Xuan-Zheng (Frontiers in Physiology, 2023)
Background and Aims: Gut smooth muscle dysfunctions contribute to symptoms such as abdominal cramping, diarrhea, and constipation in inflammatory bowel disease (IBD). The mechanisms for muscle dysfunctions are incompletely understood. We tested the hypothesis that mechanical stress plays a role in muscle dysfunction in a rat model of Crohn's-like colitis where inflammatory stenosis leads to mechanical distention in the pre-inflammation site. Methods:Crohn's-like colitis was induced by intracolonic instillation of TNBS (65 mg/kg) in Sprague-Dawley rats. Control rats were instilled with saline. The rats were fed with either regular solid food or exclusively liquid diet. Rats were euthanized by day 7. Results: When rats were fed with solid food, TNBS treatment induced localized transmural inflammation with stenosis in the instillation site and marked distention with no inflammation in the pre-inflammation site of the colon. Smooth muscle contractility was suppressed, and expression of cyclo-oxygenase-2 (COX-2) and production of prostaglandin E2 (PGE2) were increased not only in the inflammation site but also in the preinflammation site. Liquid diet treatment, mimicking exclusive enteral nutrition, completely released mechanical distention, eliminated COX-2 expression and PGE2 production, and improved smooth muscle contractility especially in the pre-inflammation site. When rats were administered with COX-2 inhibitor NS-398 (5 mg/kg, i.p. daily), smooth muscle contractility was restored in the preinflammation site and significantly improved in the inflammation site. Conclusions: Colonic smooth muscle contractility is significantly impaired in stenotic Crohn's-like colitis rats not only in the inflammation site, but in the distended pre-inflammation site. Mechanical stress-induced expression of COX-2 plays a critical role in smooth muscle dysfunction in the pre-inflammation site in Crohn'slike colitis rats.